2017
DOI: 10.1111/1462-2920.13669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Mortierella elongata and its bacterial endosymbiont Mycoavidus cysteinexigens

Abstract: Endosymbiosis of bacteria by eukaryotes is a defining feature of cellular evolution. In addition to well-known bacterial origins for mitochondria and chloroplasts, multiple origins of bacterial endosymbiosis are known within the cells of diverse animals, plants and fungi. Early-diverging lineages of terrestrial fungi harbor endosymbiotic bacteria belonging to the Burkholderiaceae. We sequenced the metagenome of the soil-inhabiting fungus Mortierella elongata and assembled the complete circular chromosome of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(199 citation statements)
references
References 98 publications
(124 reference statements)
9
183
1
Order By: Relevance
“…A phylogeny based on a concatenation of 784 single‐copy, orthologous protein sequences (Fig. ) strongly supports the erection of Mucoromycota to unite Glomeromycotina, Mortierellomycotina and Mucoromycotina (Spatafora et al ., ; Uehling et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A phylogeny based on a concatenation of 784 single‐copy, orthologous protein sequences (Fig. ) strongly supports the erection of Mucoromycota to unite Glomeromycotina, Mortierellomycotina and Mucoromycotina (Spatafora et al ., ; Uehling et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The functional genomic comparison made through KEGG pathway profile correlations (Fig. b) also showed that the sequenced Glomeromycotina present a higher metabolic similarity between taxa compared to M. elongata /Mucoromycota species, corroborating and extending M. elongata genome analysis (Uehling et al ., ). Lack of PCWDE (see next section), degradation of sucrose and glycogen (i.e.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies have provided evidence of the presence of bacteria in some Mucoromycotina, such as Endogone, where similar Mollicutes-related endobacteria have been detected (Desirò et al 2015). Endobacteria occur in the cytoplasm of Mortierellomycotina, such as Mortierella elongata (Sato et al 2010;Uehling et al 2017) and Rhizopus (Partida-Martinez and Hertweck 2005). Based on SEM micrographs, we conclude that at least some of these bacteria are epihyphal in B. adelaidae, but additional testing is necessary to determine if any of the bacteria detected on this fungus are endobiotic.…”
Section: Discussionmentioning
confidence: 99%